Scrub typhus in children: Clinical profile and complications at a Tertiary Care Teaching Hospital in Uttarakhand - Kumar, Shruti; Kumar, Mritunjay; Aggarwal, Bindu; Kumari, Rashmi (Indian Journal of Child Health, 2022)
Background: Scrub typhus is an acute febrile illness caused by rickettsia Orientia tsutsugamushi. Rickettsial infections are grossly underdiagnosed in India because of their non-specific clinical presentation, low index of suspicion among clinicians, and lack of diagnostic facilities. Objective: Objective of the study is to study the clinical profile, complications, and outcome of pediatric scrub typhus. Materials and Methods: This prospective observational study was conducted in the Department of Pediatrics, SGRR Institute of Medical and Health Sciences, Dehradun, Uttarakhand, India, over a period of 2 years from November 2013 to October 2015. Children up to 18 years of age with signs and symptoms compatible with scrub typhus along with serological confirmation were included in the study. Serological study was conducted using rapid immunochromatographic assay and/or immunoglobulin M enzyme-linked immunosorbent assay technique. Clinical presentation, laboratory findings, complications, and outcome of these children were recorded on a performa. The data were analyzed using SPSS version 20 for windows. Results: About 115 children were diagnosed as scrub typhus during the study period. All children presented with fever. Other common symptoms were myalgia (56%), vomiting (50.5%), abdominal pain (26%), headache (28%), facial puffiness (15%), and seizures (8.7%). Pallor was present in 48% of children. Other common signs were hepatomegaly (29%), splenomegaly (28%), hypotension (24%), edema (21%), oliguria (17%), maculopapular rash (10%), meningeal signs (10.4%), and conjunctivitis (3%). Thrombocytopenia (67%), anemia (51%), pleural effusion (23%), shock (16%), hepatitis (23%), acute kidney injury (17%), meningoencephalitis (10%), myocarditis (7%), and acute respiratory distress syndrome (7%) were the complications observed. Azithromycin, doxycycline or chloramphenicol were used for the treatment. Overall mortality rate was 12.2%. Conclusion: A high degree of suspicion and knowledge of geographical distribution of rickettsial diseases is crucial for its early diagnosis and favorable outcome. The presence of an eschar is a valuable clinical clue in the diagnosis of scrub typhus; however, its absence does not rule out the disease.